Introduction to microsystem packaging technology - Jin, Yufeng (CRC Press/Taylor & Francis, 2011)
The multi-billion-dollar microsystem packaging business continues to play an increasingly important technical role in today's information industry. The packaging process-including design and manufacturing technologies-is the technical foundation upon which function chips are updated for use in application systems, and it is an important guarantee of the continued growth of technical content and value of information systems.Introduction to Microsystem Packaging Technology details the latest advances in this vital area, which involves microelectronics, optoelectronics.